CASE REPORT: PERSON-CENETRED CARE AT END OF LIFE – A PHYSICIAN’S ROLE IN GUIDING PATIENT’S CARE - Quin Ng, Natalie Su (International journal of person centered medicine, 2022)
Physicians have a duty of care to act in a patient’s best interest; however, a patient’s goals of care may differ throughout different stages of their disease and at end of life.This case study aims to illustrate a physician’s role in guiding patient management at different stages in a patient with a terminal disease, while adopting a person-centred approach. The case focuses on a patient with malignant bowel obstruction (MBO) and highlights some patient-related factors for consideration in management of MBO. It also discusses the ethical considerations in the physician–patient relationship, particularly the aspect of giving information regarding treatment options and addresses the concept of “individualized” goals of care. Person-centred care is dynamic and a clinician may need to adjust their role in providing person-centred care according to different stages of a patient’s disease.